2019
DOI: 10.3390/vaccines7040133
|View full text |Cite
|
Sign up to set email alerts
|

Historical H1N1 Influenza Virus Imprinting Increases Vaccine Protection by Influencing the Activity and Sustained Production of Antibodies Elicited at Vaccination in Ferrets

Abstract: Influenza virus imprinting is now understood to significantly influence the immune responses and clinical outcome of influenza virus infections that occur later in life. Due to the yearly cycling of influenza viruses, humans are imprinted with the circulating virus of their birth year and subsequently build a complex influenza virus immune history. Despite this knowledge, little is known about how the imprinting strain influences vaccine responses. To investigate the immune responses of the imprinted host to s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…Furthermore, it has been proposed that influenza viruses that circulate during a person's childhood can confer lasting protection against new influenza viruses that belong to a similar phylogenetic group [24]. In this regard, ferrets that were vaccinated with a split-virion influenza vaccine following influenza A (H1N1) A/USSR/90/1977 infection earlier in their life showed less illness after infection with influenza A (H1N1)pdm09 A/California/07/2009 as compared with vaccinated ferrets who were not previously infected with influenza A (H1N1) A/USSR/90/1977 [25]. Moreover, it was recently shown that recurring exposures to influenza A (H3) in humans was associated with higher antibody titers, enhanced antibody affinity, as well as enhanced antibody avidity following influenza vaccination, as compared with individuals not previously exposed [26].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been proposed that influenza viruses that circulate during a person's childhood can confer lasting protection against new influenza viruses that belong to a similar phylogenetic group [24]. In this regard, ferrets that were vaccinated with a split-virion influenza vaccine following influenza A (H1N1) A/USSR/90/1977 infection earlier in their life showed less illness after infection with influenza A (H1N1)pdm09 A/California/07/2009 as compared with vaccinated ferrets who were not previously infected with influenza A (H1N1) A/USSR/90/1977 [25]. Moreover, it was recently shown that recurring exposures to influenza A (H3) in humans was associated with higher antibody titers, enhanced antibody affinity, as well as enhanced antibody avidity following influenza vaccination, as compared with individuals not previously exposed [26].…”
Section: Discussionmentioning
confidence: 99%
“…Emphasis was placed on the concept that testing vaccine candidates in naïve ferrets do not reflect the performance of the vaccines in the human population. In an A(H1N1) primed model, greater protection after vaccination was observed [18].…”
Section: Contemporary A(h1n1)/a(h3n2) Modelsmentioning
confidence: 98%
“…The first influenza strain that infects a human or animal is the imprinting virus for that individual [5,18]. This initial strain biases the immune memory response to subsequent infections in a phenomenon described as "original antigenic sin".…”
Section: Influenza Pre-immunity In the Human Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated in Figure 1, ferrets are naturally susceptible to human H1N1pdm09 and H3N2 influenza virus infections. To develop a model to mimic the yearly seasonality of influenza infections, we waited between 60 and 84 days between infections to allow for the primary immune response to wane, as shown by others (19)(20)(21)(22), and result in two robust infections. Six ferrets were infected with H3N2 virus and then three of those animals were experimentally infected at 60 days post-infection with H1N1pdm09 virus (herein referred to as 'H3-H1 INF') ( Fig 2A).…”
Section: Iav Transmission To Naive Animals Is Efficient After Short Amentioning
confidence: 99%